Targeting Cardiac Myocyte Na+-K+ Pump Function With β3 Adrenergic Agonist in Rabbit Model of Severe Congestive Heart Failure. (September 2020) - Fry, Natasha A.S.; Liu, Chia-Chi; Garcia, Alvaro; Hamilton, Elisha J.; Karimi Galougahi, Keyvan; Kim, Yeon Jae; Whalley, David W.; Bundgaard, Henning; Rasmussen, Helge H.
Abstract : Background: Abnormally high cytosolic Na + concentrations in advanced heart failure impair myocardial contractility. Stimulation of the membrane Na + -K + pump should lower Na + concentrations, and the β3 adrenoceptor (β3 AR) mediates pump stimulation in myocytes. We examined if β3 AR-selective agonists given in vivo increase myocyte Na + -K + pump activity and reverse organ congestion in severe heart failure (HF). Methods: Indices for HF were lung-, heart-, and liver: body weight ratios and ascites after circumflex coronary artery ligation in rabbits. Na + -K + pump current, Ip, was measured in voltage-clamped myocytes from noninfarct myocardium. Rabbits were treated with the β3 AR agonists CL316, 243 or ASP9531, starting 2 weeks after coronary ligation. Results: Coronary ligation caused ascites in most rabbits, significantly increased lung-, heart-, and liver: body weight ratios, and decreased Ip relative to that for 10 sham-operated rabbits. Treatment with CL316, 243 for 3 days significantly reduced lung-, heart-, and liver: body weight ratios and prevalence of ascites in 8 rabbits with HF relative to indices for 13 untreated rabbits with HF. It also increased Ip significantly to levels of myocytes from sham-operated rabbits. Treatment with ASP9531 for 14 days significantly reduced indices of organ congestion in 6 rabbits with HF relative to indices of 6 untreated rabbits, and it eliminated ascites. β3 AR agonists did not significantly change heart rates or blood pressures. Conclusions: Parallel β3 AR agonists-induced reversal of Na + -K + pump inhibition and indices of congestion suggest pump inhibition is a useful target for treatment with β3 AR agonists in congestive HF. Abstract : Supplemental Digital Content is available in the text.